Miswak as an Alternative Treatment Modality in Medicine and Dentistry: A review - Deswal, Himanshu; Singh, Yogender; Grover, Harpreet Singh; Bhardwaj, Amit (Innovare Journal of Life Sciences, 2016)
Herbal chewing sticks, commonly known as Miswak, are among the ancient and traditional oral hygiene aids. It is considered as Nature's little toothbrushâ€ as it is a popular chewing stick throughout Indian subcontinent. Nowadays, because of low cost, free availability, unique chemical composition, and spiritual beliefs, miswak is being used worldwide.Â  It also serves as a natural toothpaste with antibacterial, anti-caries, anti-periopathic disinfectant having anti-plaque and anti-fungal properties and it can be used effectively as a natural tool for teeth cleansing and as a natural analgesic for the disturbing toothache. This review gives a bird's eye view mainly on the biological activities of the miswak and plausible medicinal and dental applications.